Evaluation of cardiovascular risk factors for medical workers of an urban multidisciplinary hospital - K. G. Tkachenko; A. D. Erlikh; A. N. Atakanova; N. R. Aripova; M. Yu. Butusova; K. B. Kurbanova; R. M. Orlovskaya; N. V. Pashkevich; K. R. Pushkareva; M. V. Rodina; D. T. Shakhbolatova; O. A. Kislyak (Кардиоваскулярная терапия и профилактика)
Aim. To assess the prevalence of various risk factors (RF) for cardiovascular diseases (CVD) among employees of a multi-field hospital (Moscow City Clinical Hospital № 29).Material and methods. We determined blood pressure, weight, height, waist circumference, blood lipid and glucose levels, and used specially created questionnaire. At least 322 medical workers aged >40 years were examined.Results. The average age of the subjects was 51,6+7,8 years, among them 21% of doctors, 47% of nurses; 91% of women. 50% of subjects had arterial hypertension in the history, 40% — high blood pressure >140/90 mm Hg (56% of them regularly received antihypertensive drugs). The frequency of other RF of CVDs was as follows: low physical activity — 74%, hyperlipidemia — 69%, excessive salt intake — 68%, obesity — 43%, unhealthy diet — 37%, smoking — 25%. Among allemployees taking acetylsalicylic acid, 80% took it without invariable indications for this. Among persons with invariable indications for statins, the drug of this class was taken by 11%. When comparing indicators in women of different ages, it was found that the frequency of behavioral RF (unhealthy diet, excessive salt intake, low physical activity) in women <50 years was not significantly different from that in women >50 years; smoking in younger women was higher.Conclusion. A survey of medical workers aged >40 years revealed a high frequency of well-known modified RF of CVDs, especially low physical activity, hyperlipidemia, excessive salt intake, and obesity. The prevalence of arterial hypertension, smoking and unhealthy diet in the studied group were also high, but on average did not exceed the same numbers of general Russian population. We determined high frequency of aspirin intake without invariable indications, and low frequency of statins use in individuals with invariable indications, as well as a low efficacy of drug treatment of arterial hypertension.